The Effect of Return on Equity and Company Size on Stock Prices through Dividend Payout Ratio - Gina Nurhayati; Asep Muhammad Ramdan; Nor Norisanti (Jurnal Ilmiah Manajemen Kesatuan, 2026)
A decline in share prices among manufacturing companies listed on the Indonesia Stock Exchange (IDX) indicates pressure on corporate performance and investor perceptions within the capital market. This study analyzes the impact of Return on Equity (ROE) and company size on share prices, utilizing the Dividend Payout Ratio (DPR) as a mediating variable. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. The study selects the sample using purposive sampling from manufacturing corporations listed on the IDX in 2024. The empirical results indicate that return on equity exerts a positive and significant effect on the dividend payout ratio but does not significantly affect share prices. Conversely, company size has a positive and significant effect on share prices, while it displays a negative and significant influence on the dividend payout ratio. Furthermore, the dividend payout ratio has a negative and significant impact on share prices. Mediation analysis reveals that the dividend payout ratio fails to mediate the effect of return on equity on share prices. However, it significantly mediates the impact of company size on share prices.